2007
DOI: 10.1111/j.1525-1594.2007.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Bioartificial Liver Using the Radial‐flow Bioreactor in Treatment of Fatal Experimental Hepatic Encephalopathy

Abstract: An extracorporeal bioartificial liver (BAL) that could prevent death from hepatic encephalopathy in acute hepatic insufficiency was aimed to develop. A functional human hepatocellular carcinoma cell line (FLC-4) was cultured in a radial-flow bioreactor. The function of the BAL was tested in mini-pigs with acute hepatic failure induced by alpha-amanitin and lipopolysaccharide. When the BAL system was connected with cultured FLC-4 to three pigs with hepatic dysfunction, all demonstrated electroencephalographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…Culture conditions were employed as reported previously (20,36,37). Briefly, A431 cells (1x10 7 cells) that had been injected in the reservoir of the RFB system were trapped by adherence to the matrix and then continuously cultured with 150 ml of RPMI-1640 medium supplemented 10% FBS in a CO 2 incubator (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture conditions were employed as reported previously (20,36,37). Briefly, A431 cells (1x10 7 cells) that had been injected in the reservoir of the RFB system were trapped by adherence to the matrix and then continuously cultured with 150 ml of RPMI-1640 medium supplemented 10% FBS in a CO 2 incubator (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to CA9 protein expression under hypoxia in the living body, in vitro regulation of the protein expression is reported to be positively related to dense culture (78,79). In order to determine whether or not CA9 molecular induction in 3D cultured cells was dependent on the increasing cell density, the effects of cell density on CA9 protein expression levels were analyzed using a 2D, monolayer culture dish, the RFB and other culture devices to provide spheroid culture conditions, since 3D culture in the RFB has been known to culture cells at a high density while mimicking the in vivo architecture (37,80). Results showed that the increased protein levels of CA9 at various degrees under 3D culture conditions in all devices yielded cell densities at lower than 50% confluence and showed non-significant cell density-dependent induction of CA9 mRNA expression during the period of the experiment in the 2D cultured cells (Fig.…”
Section: Increased Expression Of Ca9 In Cultured Cells Under 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…При наличии пористого носителя (подложки), гепатоциты могут функционировать внутри него, при этом они защищены от раневого стресса, что позволяет использовать более высокие скорости перемешивания и аэрации в процессе культивирования. В этом качестве были исследованы различные материалы, в том числе полиуретановая пена [95], поливиниловая смола [96], альгинатные частицы [97], пористый гидроксиапатит [98] и полиэфирные скаффолды [99].…”
Section: системы с "уплотнённым слоем" (Packed Bed System)unclassified
“…In our laboratory, several cell lines derived from hepatocellular carcinoma culture in a radial flow type bioreactor (RFB), which is a type of 3D culture system with a high density cell population, showed not only improved cell functions, but also a differentiated morphology as compared with those grown in 2D culture (5,(9)(10)(11). A representative result demonstrating the functional effectiveness of this system was that use of the RFB system to culture functional liver cells cured a mini-pig with amanitin-, galactosamine-induced acute liver failure as it served as an artificial liver system (10).…”
Section: Introductionmentioning
confidence: 99%